1995
DOI: 10.1111/j.1365-3083.1995.tb03713.x
|View full text |Cite
|
Sign up to set email alerts
|

Lyme Neuroborreliosis: Evidence for Persistent Up‐Regulation of Borrelia Burgdorferi‐Reactive Cells Secreting Interferon‐γ

Abstract: The T-cell response to the aetiologic pathogen Borrelia (B.) burgdorferi in patients with Lyme neuroborreliosis (LN) and in control patients with other neurological diseases was examined by enumerating B. burgdorferi-reactive T cells secreting interferon-gamma (IFN-gamma) with an ELIspot assay. LN patients had elevated numbers of B. burgdorferi-reactive IFN-gamma secreting cells in blood and approximately 20-fold enriched in the cerebrospinal fluid (CSF). A positive correlation existed in CSF between B. burgdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Interestingly, in paired samples of serum and CSF, levels of IL‐6 were significantly higher in the CSF than in serum ( P <0·001), suggesting that the IL‐6 production is intrathecal, and compartmentalized to the CNS. Similar findings of compartmentalization of immune responses in borreliosis have previously been reported 14,15 , 32 . One reason for finding lower IL‐6 levels in CSF from patients with Lyme borreliosis compared to controls could be that IL‐6 is in fact increased in our controls.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, in paired samples of serum and CSF, levels of IL‐6 were significantly higher in the CSF than in serum ( P <0·001), suggesting that the IL‐6 production is intrathecal, and compartmentalized to the CNS. Similar findings of compartmentalization of immune responses in borreliosis have previously been reported 14,15 , 32 . One reason for finding lower IL‐6 levels in CSF from patients with Lyme borreliosis compared to controls could be that IL‐6 is in fact increased in our controls.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, early treatment with recombinant IL-4 cured the susceptible animals [10]. Th1-like responses in human borreliosis have been reported by us and others [12][13][14][15]. Th1-like responses in human borreliosis have been reported by us and others [12][13][14][15].…”
Section: Introductionmentioning
confidence: 98%
“…a weak initial inflammatory response, not generating proper down-regulatory feedback mechanisms. Indeed, previous investigations in both mice [16], [17] and humans [18][21] have indicated that a successful clinical outcome requires an effective inflammatory T helper cell (Th) 1-type response that is adequately balanced by an anti-inflammatory and Th2-like response against B. burgdorferi .…”
Section: Introductionmentioning
confidence: 99%